Comparison of Incidences of Serious Diseases within Regions in the Czech Republic - Kopecká, Lucie; Zapletal, David; Pacáková, Viera (My University, 2020)
The incidence of serious diseases in most European countries has a growing trend compared to mortality due to these illnesses. There are significant differences in the health status of the population not only between countries but also within them. The goal of the health policy of the European Union and its member states is not only to reduce the incidence of serious diseases but also mitigate regional inequalities of their incidence. The object of this article is to compare incidences of serious diseases within the regions in the Czech Republic by using hybrid approach which combine multidimensional scaling with linear ordering of the objects. Hybrid approach is suitable for visualization of objects and determination of distances from ideal object according to indicators used. The factors of regional inequalities in the incidence of serious diseases are identified and quantified based on the results of hybrid method.
Porovnání výskytů závažných onemocnění v rámci regionů v České republice
Keywords: incidences; serious diseases; multidimensional scaling; linear ordering; hybrid approach; rank correlation; factor analysis; výskyty; závažná onemocnění; vícerozměrné škálování; lineární uspořádání; hybridní přístup; pořadová korelace; faktorová analýza